Email from George Matsuyama to Pat A. Ashton - Matsuyama, George (2000)
This email describes an attempt to develop a glucose electrode in the 1960s. This project was abandoned when Beckman Instruments focused instead on the Glucose Analyzer.
Keywords: Electrodes; Glucose--Analysis; Blood sugar; Scientific apparatus and instruments; Beckman Instruments, Inc.